Navigare – The Inauguration of Arken in 1996 - Christoffersen, Erik Exe (Peripeti, 2017)
Navigare (1996) was specifically created for the inauguration of ARKEN - Museum of Modern Art as a ‘baptismal’act in the name of art in time and space.